2013
DOI: 10.3174/ajnr.a3631
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial-Derived Atherosclerosis Assessment: An In Vitro Comparison between Virtual Histology by Intravascular Ultrasonography, 7T MRI, and Histopathologic Findings

Abstract: BACKGROUND AND PURPOSE: Atherosclerotic plaque composition and structure contribute to the risk of plaque rupture and embolization. Virtual histology by intravascular ultrasonography and high-resolution MR imaging are new imaging modalities that have been used to characterize plaque morphology and composition in peripheral arteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
46
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 32 publications
2
46
0
Order By: Relevance
“…Evidence from the comparative studies between HRMRI and histology has supported that intracranial eccentric wall lesions represent the pathology of atherosclerosis (7,(9)(10)(11). In this study, a high percentage (80.3%) of Chinese young patients with unilateral MCA stenosis had such eccentric wall lesions on HRMRI.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Evidence from the comparative studies between HRMRI and histology has supported that intracranial eccentric wall lesions represent the pathology of atherosclerosis (7,(9)(10)(11). In this study, a high percentage (80.3%) of Chinese young patients with unilateral MCA stenosis had such eccentric wall lesions on HRMRI.…”
Section: Discussionsupporting
confidence: 57%
“…Emerging studies have suggested that HRMRI is reliable for detecting intracranial artery wall lesions, consistent with histology findings (7)(8)(9)(10)(11). On HRMRI, eccentric stenosis is suggestive of atherosclerosis while concentric stenosis is suggestive of non-atherosclerotic diseases, although overlap may occasionally exist (3,8,(12)(13)(14).…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…Only a few histology validation studies have been undertaken at 7T. [15][16][17] The scan parameters of multicontrast MR imaging in this study were close to those in standard protocols used in clinical in vivo studies at 3T, except that this study used higher resolution settings. 9,26 Therefore, the criteria established in this study (Table 1) could be used when assessing images obtained in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have reported ex vivo MR imaging characteristics of intracranial plaque with 7T research scanners. [15][16][17] However, these results cannot be transferred to 3T for the clinical evaluation of intracranial arterial disease because the MR relaxometry is different at 3T and 7T. Very few studies have reported intracranial plaque characteristics at 3T, the highest field strength that is clinically relevant.…”
mentioning
confidence: 99%